2018
DOI: 10.1167/iovs.18-24227
|View full text |Cite
|
Sign up to set email alerts
|

Slowed Dark Adaptation in Early AMD: Dual Stimulus Reveals Scotopic and Photopic Abnormalities

Abstract: PURPOSE. The recovery of visual sensitivity after a photobleach in early AMD is slowed in rods but cones also may be abnormal. The purpose of this article was to test different stimulus locations to investigate cone function and its relation to rod abnormalities. METHODS.Stimuli were presented at two locations, 3.08 and 5.58, in the inferior visual field. Post photobleach dark adaptation (DA) curves from 50 early-AMD patients were compared with those from 15 healthy controls of similar age. Curves were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…By studying mesopic vision to include both rod and cone responses, it becomes clear that rods play a role in colour vision, and not just light adaptation. The differing characteristics of rods vs cones for light level, wavelength, retinal eccentricity, and temporal and spatial aspects of vision result in functional differences between controls and patients with AMD for scotopic, mesopic, and photopic mechanisms, along with adaptation, colour contrast, acuity, etc …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By studying mesopic vision to include both rod and cone responses, it becomes clear that rods play a role in colour vision, and not just light adaptation. The differing characteristics of rods vs cones for light level, wavelength, retinal eccentricity, and temporal and spatial aspects of vision result in functional differences between controls and patients with AMD for scotopic, mesopic, and photopic mechanisms, along with adaptation, colour contrast, acuity, etc …”
Section: Discussionmentioning
confidence: 99%
“…The differing characteristics of rods vs cones for light level, wavelength, retinal eccentricity, and temporal and spatial aspects of vision result in functional differences between controls and patients with AMD for scotopic, mesopic, and photopic mechanisms, along with adaptation, colour contrast, acuity, etc. 95,96 In addition to retinal remodelling that occurs with loss of neurons, 84 there is the potential for binocular summation or inhibition, with differences due to binocular disparity, spatial frequency, and eccentricity. 97 In patients with geographic atrophy and AMD, potential vision is not accurately assessed by limiting measurements only to initial ones.…”
Section: Discussionmentioning
confidence: 99%
“…DA was measured psychophysically using a PC-based system as previously described. 39,40,[54][55][56][57] The test was conducted monocularly in the study eye. The subjects wore their best optical correction for the test distance (90 cm), and the fellow eye was covered using an eye patch.…”
Section: Dark Adaptationmentioning
confidence: 99%
“…There is a sound physiologic basis for this. 49 Such techniques were used in the investigation of dry AMD by Jackson et al, 50 Murray et al, 51 and, more recently, Tahir et al, 40 who confirmed the existence of both photopic and scotopic abnormalities in early AMD.…”
mentioning
confidence: 99%
See 1 more Smart Citation